Deflection of microcantilever by growing vapor bubble - Lee, Heon Ju; Chang, Young Soo; Lee, Yoon Pyo; Jeong, Kwang-Hun; Kim, Ho-Young (ELSEVIER SCIENCE SA, 2007)
This work investigates the mechanics of microcantilever deflection due to growth of a vapor microbubble. We construct a theoretical model to predict the elastic beam deflection due to the capillary pressure developed by the bubble growing between the beam and a substrate. The theory is in good agreement with our experimental results in both macro- and micro-scales. The deflection of a thin-solid structure due to growing bubbles can be used in such micromachines as microactuators, microgenerators and micropumps, which are operated as immersed in liquid. (C) 2007 Elsevier B.V. All rights reserved.